Rapid Determination of Pharmacokinetic Properties of New Chemical Entities: In vivo Approaches - Cox, K.A.; White, R.E.; Korfmacher, W.A. (Combinatorial Chemistry & High Throughput Screening, 2002)
There is a continuing need for increased throughput in the evaluation of new chemical entities in terms of their pharmacokinetic (PK) parameters as part of new drug discovery. This review summarizes various approaches that have been used to increase throughput in this area. The article divides the approaches into two areas: assay enhancement and sample reduction.
Keywords: Pharmacokinetic pk